2016
DOI: 10.4236/odem.2016.42004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Occupational Asthma in Tunisia: Results of a First National Study

Abstract: Introduction: Apart from its increasingly important frequency, occupational asthma (OA) has become the most important cause of occupational respiratory disorders in developed countries. The number of etiological agents continues to grow following the constant introduction of new harmful substances in industry. Objectives: Determine the prevalence and incidence of OA in our country, the socio-occupational characteristics of asthmatics, and study the forensic and social impact of such pathology. Material and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In Tunisia, OA occurs frequently among workers in the textile sector, which is a highly developed sector in the region of the Tunisian center. OR was associated with asthma in 40.7% of cases [10].…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…In Tunisia, OA occurs frequently among workers in the textile sector, which is a highly developed sector in the region of the Tunisian center. OR was associated with asthma in 40.7% of cases [10].…”
Section: Methodsmentioning
confidence: 92%
“…Concerning the textile sector, several studies have cal data on the prevalence of OA and OAR are not available since most of the studies conducted in Tunisia express the prevalence of the pathology within a particular sector, or a group exposed to the same etiologic agent. A retrospective descriptive study of all cases of asthma reported in the private sector in the region of center of Tunisia and recognized as occupational disease during a nine-year period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) showed that the association between asthma and allergic rhinitis was found in 42.9% of cases [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations